Analisis Postur Kerja pada Operator Sortasi di Pabrik Kelapa Sawit dengan Metode RULA dan REBA di PT. London Sumatra, Tbk Begerpang Palm Oil Mill - Tarigan, Harri Pratama; Hasibuan, Yetti Meuthia; Utama, Denny Wallady (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
This research aims to identify the body parts of palm oil sorting workers that most often experience problems, as well as determining the need for work improvements in the sorting process. Apart from that, this research also aims to design a tool that can correct the operator's working posture, thereby reducing the risk of musculoskeletal disorders. The research results showed that based on the Nordic Body Map questionnaire, the highest complaints of pain were reported in the waist with a percentage of 100%, while 66.6% of respondents reported pain in the back and left wrist. Analysis using the RULA method revealed that the three respondents obtained a final score of 7, which indicates a high level of risk and requires immediate action. Meanwhile, analysis using the REBA method shows that two workers have a final score of 8 (high risk) and one worker has a final score of 10 (very high risk), all of which require immediate action. After the proposed work posture improvements, the final REBA score decreased from 10 to 7, indicating a decrease in the risk level from high to moderate. However, the final score of RULA remained 7, indicating that improving the proposed posture did not change the final results of RULA. This conclusion emphasizes the importance of immediate treatment of unergonomic work postures to reduce musculoskeletal risks in palm oil sorting workers.